(3GdcJjHI GdcGefI ajef dbjfGg HGdCfOdS ef TYQGA GdeGFI GdKGefIs - (3CHh YHO Gddg dSGf GdOjf eMeO Hf YHO Gddg Hf SYjO GHf GdNWjH GdZQfGWi GdCfOdSj,J (B776 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GdCOH aj LejY eG ddafhf ef GdCShGb aGcgI TgjI GdCPhGb s
(3BNQgG (B:s
(3hLOJ aj fSNI YJjbI LOkG HNW HYV GdYdeGA YbH gPg GdCHjGJ eGUhQJg (B: (3GdMeO ddg hLOJ HGdCUd gfG eG fUg Edi gfG JhLO gPg GdcJjHI, hdYd eDdagG CNJQJg GdefjI bHd JeGegG hGddg JYGdi CYde s
(3GfXQ Qbe (B763 (3JGQjNs
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B235s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B372 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B343 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs